Respuesta :

Answer:

Given the reference to the chain rule, I assuming by "calculate", you mean "take the derivative of", in which case we have:

For the first function:

[tex]y = (2u^2 + 3)^{\frac{1}{3}}\\\\\frac{dy}{du} = \frac{1}{3}(2u^2 + 3)^\frac{-2}{3}(4u)\\\\\frac{dy}{du} = \frac{4u}{3}(2u^2 + 3)^\frac{-2}{3}\\\\\frac{dy}{du} = \frac{4u}{3(2u^2 + 3)^\frac{2}{3}}[/tex]

and for the second one:

[tex]u = \sqrt{2x + 1}\\\\u = (2x + 1)^{0.5}\\\\\frac{du}{dx} = 0.5(2x + 1)^{-0.5}(2)\\\\\frac{du}{dx} = \frac{1}{\sqrt{2x + 1}}[/tex]

ACCESS MORE